Maximal oxygen transport to the muscle cell oin altitude natives - Lundby, C. (International hypoxia symposia 2009. Hypoxia and exercise. 10-14 March 2009, 2009)
In hypoxia aerobic exercise performance of high altitude natives is suggested to be superior to that of lowlanders, i.e. for a given altitude natives are reported to have higher maximal oxygen uptakes (VO2max). The likely basis for this is a higher pulmonary diffusion capacity, which in turn ensures higher arterial O2 saturations (SaO2) and therefore also potentially a higher delivery of O2 to the exercising muscles. This review focuses on O2 transport in high altitude Aymaras. We have quantified femoral artery O2 delivery, arterial O2 extraction and calculated leg VO2 in Aymara, and compared their values with that of acclimatizing Danish lowlanders. All subjects were studied at 4,100 m. At maximal exercise Sa02 dropped tremendously in the lowlanders, but did not change in the Aymara. Therefore arterial 02 content was also higher in the Aymara. At maximal exercise however, fractional O2 extraction was lower in the Aymara, and the a-vO2 difference was similar in both populations. The lower extraction levels in the Aymara were likely the result of a lower muscle O2 conductance {a measure of muscle diffusion capacity). At any given submaximal exercise intensity, leg VO2 was always of similar magnitude in both groups, but at maximal exercise the Danes had higher leg blood flow, and hence also higher maximum leg VO2. With the induction of acute normoxia fractional arterial O2 extraction fell in the highlanders, but remained unchanged in the Danes. Hence high altitude natives seem to be more diffusion limited at the muscle level as compared to lowlanders. In conclusion Aymaras preserve SaO2 very high during hypoxic exercise (like due to a higher diffusion capacity), but the effect hereof on V02max is reduced by a lower ability to extract O2 at the muscle level.